Making nutrition labels more evaluable: A qualitative research study exploring equivalence framing for energy density to support chronic disease prevention - Lauren Bayliss (Health Literacy and Communication Open)
Background Calorie and serving size, which are interpreted together as energy density, are commonly used by individuals seeking to eat healthily. Choosing low energy-dense foods allows people to consume fewer calories even without intending to do so. However, numeracy skills and denominator neglect (the tendency to ignore the bottom half of a ratio) can make energy density information difficult to interpret. Equivalence framing, the use of the same data in a different format, may make energy density information more intuitive.Aims This study explores perceptions and use of nutrition information by consumers. The information is then used to explore how energy density information could be framed in ways that are equivalent but more evaluable.Methods A qualitative approach was taken to understand how nutrition labels are perceived. In-depth, semi-structured interviews were conducted in the United States with 34 women of different levels of socioeconomic status. Transcripts were analyzed using thematic analysis, and both theoretically grounded and emergent themes were examined.Findings Calorie information was highly salient for most participants, but the associated serving size was not. Even highly educated interviewees reported making mistakes related to serving size, such as overlooking it when interpreting calorie numbers. Some serving size measures, such as cups and counts, were easier for some interviewees to use when making food choices than others, such as measures of weight. Interviewees also discussed nutrients in relation to calories, including the use of a 2,000-calorie diet.Discussion Consumers preferred serving measures that they could visualize. For example, participants who regularly cooked preferred cup measures. However, even women who regularly used measures of weight did not like servings in grams or ounces. Because serving size was so often overlooked, the use of a set serving size across different food categories may be more useful than the variable serving size currently used in the United States. Alternatively, however, flipping the energy density ratio (providing serving size per a set number of calories) might also help participants overcome the error of denominator neglect.